PEMANFAATAN APLIKASI QUIZIZZ SEBAGAI MEDIA GAME BASED LEARNING (Dalam Meningkatkan Konsentrasi Siswa Dalam Belajar Matematika Pada Matei Eksponen Di Mts Fathus Salafi Putri Mangaran Situbondo) - Astindari, Tri; Hasanah, Nur (Biro 3 Kemahasiswaan dan Kerjasama Universitas Abduracman Saleh Situbondo, 2024)
Currently, technology is developing very quickly and cannot be avoided. However, this technology must be utilized as well as possible. One of the game-based learning that can increase students' concentration in learning is by using Quizziz, which is very young for students to use because it uses technology that can support students' concentration. Based on the results of observations, it was found that many students lacked concentration in doing mathematics. This research uses experimental research, namely conducting experiments in two classes with different treatments and obtained. Based on the average score of both classes. Groups taught using modelsPBLhad an average of 80, while the group taught using the discussion method had an average of 70. The results of the researcher's testing using the Independent Sample T-Test test obtained a Sig. (2-tailed) namely 0.033 < 0.05 and the calculation results show that .